The functional approach in teaching geography in the Moroccan primary school between perception and reality of practice - AOUIDATE, Rachida Allal; Boubria, AbdElouahed; AAFIR, Mustapha (Journal of Educational and Psychological Sciences, 2022)
In light of scientific progress and the explosion of knowledge that the world is witnessing, the school in general and the subjects in particular, including geography subject, have become questionable about their contribution to preparing students for daily life. Educational geography must mark a break with geography / the wheel, which can be summed up in the copy of data and knowledge. And it must keep pace with the development of global geographical thought, as well as developments at the level of the didactic field, to establish a didactic approach to teaching geography that stems from clarifying the nature of the intellectual processes performed by geographers and making students in a position to practice those operations on their environment during the training, so that they acquire mechanisms of scientific methodological thinking and their practice in their relationship with their living environment.In order for educational geography to play the role entrusted to it, it is necessary to unify the teachers' awareness of it and its pivotal role in forming the learners’ systematic thinking. Therefore, we tried, through our research, to unveil the teachers' representations about geography as a science, as a subject, and about the way it is taught. Because it affects their classroom practices and the purpose of their inclusion in school subjects. Thus, the results of the research will constitute a starting point for reconsidering the teacher’s representations and working to form a unified understanding of the concept of geography. Its results will also constitute the beginning of future researches on the impact of teachers' misrepresentations on classroom practice, didactic transmission, achieving goals.
Keywords: Educational Geography; Approach; Functional; Teaching Geography